In-depth numerical analysis of combustion and NOx emission characteristics in a 125 MWe biomass boiler. (15th January 2023) - Thieu Trinh, Viet; Kim, Seung-Mo; Kim, Kang-Min; Lee, Byoung-Hwa; Jeong, Tae-Yong; Son, Ju-Seong; Kim, Jong-Man; Jeon, Chung-Hwan
Highlights: A retrofit 125MWe Yeongdong boiler is adopted of burning 100% biomass. A 3D numerical simulation performs in-depth combustion and NOx emission behaviour. The rate of volatile burnout is significantly higher and faster than that of char burnout. Thermal NOx emissions account for most biomass combustion-associated emissions. Char conversion is dependent on burner position and particle size. Abstract: A 125MWe Yeongdong retrofit boiler burning 100 % biomass was adopted for electricity generation to achieve net zero energy emissions by 2050. However, the high volatile content of biomass affects temperature distribution and NOx mechanism compared to coal. Additionally, the wide range of particle size inlet results in large amounts of ash at the hopper and high unburned carbon of bottom ash. Here, an in-depth 3D numerical simulation was performed for the combustion and nitrogen oxides (NOx) emission behavior in the biomass boiler. The effect of biomass particle size, active burners on the char conversion at the boiler and bottom outlet, and particle residence time were assessed to determine the particle size range. The simulation results were validated by comparison with the actual data. The volatile burnout rate was significantly higher and faster than that of char burnout, and the burner throat exhibits the highest temperature range (approximately 1800–2100 K). Regarding NOx emission, the rate of thermal NOx was higher than that of total NOx, and the reduction of NOx was also significantly high to contribute the low NOx emission at boiler outlet. In addition, char conversion had significantly depended on the position of the active burner, and particle size below 665 μm can be entrained upward to the boiler outlet with char conversion over 96.85 % at boiler outlet and 100 % at bottom hopper. Therefore, analysis on each active burner can be used to find optimal standby burner while the particle size analysis suggested that percentage of particles larger than 665 μm should be reduced in the biomass boiler. The high-temperature propensity can aid in understanding the deposition behavior in biomass boilers.